2021
DOI: 10.3390/toxins13020110
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fusarium Mycotoxins and Their Modified Forms in Forage Maize Cultivars

Abstract: Forage maize is often infected by mycotoxin-producing Fusarium fungi during plant growth, which represent a serious health risk to exposed animals. Deoxynivalenol (DON) and zearalenone (ZEN) are among the most important Fusarium mycotoxins, but little is known about the occurrence of their modified forms in forage maize. To assess the mycotoxin contamination in Northern Germany, 120 natural contaminated forage maize samples of four cultivars from several locations were analysed by liquid chromatography-high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 79 publications
(172 reference statements)
3
21
1
Order By: Relevance
“…exceeded 20 μg/kg of AF (Ogunade et al, 2018). In our research, average DON concentrations were not only lower than those informed in previous studies (Birr et al, 2021;Eckard et al, 2011), but were also reduced by the inoculant.…”
Section: Discussioncontrasting
confidence: 69%
“…exceeded 20 μg/kg of AF (Ogunade et al, 2018). In our research, average DON concentrations were not only lower than those informed in previous studies (Birr et al, 2021;Eckard et al, 2011), but were also reduced by the inoculant.…”
Section: Discussioncontrasting
confidence: 69%
“…As these masked mycotoxins are often not included in chemical analyses, reported mycotoxin content can represent an underestimation of actual levels [75]. In our study, we did not analyze these masked mycotoxins, even though they have already been reported in maize fields in Belgium and northern Germany, where the presence of the masked form was positively correlated with the parent compound [66,76]. Therefore, future analyses of maize silages should include these masked forms to better understand the kinetics of conjugated mycotoxins during the silage process and to better determine the risk for dairy cows.…”
Section: Discussionmentioning
confidence: 94%
“…When considering corn silage, 3.4% of samples exceeded the EC limit of 8000 µg/kg while 1.9% exceeded the 10,000 µg/kg FDA advisory level for grains for poultry and ruminants, which should not exceed 50% in the final ration. Similarly, Birr et al [ 21 ] reported that 9% of corn silage from Germany exceeded 5000 µg/kg. Despite fewer samples having very high DON levels, we did find that the mean concentration of DON in corn grain samples was 840 µg/kg.…”
Section: Discussionmentioning
confidence: 97%